KERJA SAMA DIREKTORAT JENDERAL BEA CUKAI (DJBC) DENGAN THE GENERAL ADMINISTRATION OF CHINA CUSTOMS (GACC) DALAM UPAYA MENGATASI PENYELUNDUPAN NARKOBA DI INDONESIA: STUDI KASUS BEA CUKAI TANJUNG EMAS - Lukitasari Prima Dewi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
Drug smuggling is an organised transnational crime that has reached the global emergency stage. Indonesia as a sovereign country, Indonesia must protect its national interest by surmounting the drug smuggling that enters Indonesian territory. Therefore, Indonesia established cooperation with China in the field of customs, which is between the Indonesian Directorate General Of Customs And Excise and the General Administration China Customs. The research objective is to explain and give an understanding of bilateral cooperation between the Indonesian Directorate General of Customs and Excise and the General Administration China Customs to surmount drug smuggling. The research method that is used is the qualitative method of research. This research has the quality of being descriptive and analytic. The theory used in this research is trans governmental networks and securitisation. This research shows that although cooperation between the two country’s customs offices, the drug smuggling rate still exists. The causes are high demand within the country, limited transparency and the domestic political system.